2013
DOI: 10.1016/j.ijrobp.2012.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Distribution of Fluorodeoxyglucose-Avid Para-aortic Lymph Nodes in Patients With Cervical Cancer

Abstract: Summary This study presents a map of PET-positive paraaortic nodes (PAN) in cervical cancer. Available information about the location of PAN metastases in cervical cancer is not adequately detailed to guide treatment planning for highly conformal radiation therapy. Our population based atlas outlines the spatial distribution of these lymph nodes to facilitate target delineation and treatment planning. Suggested clinical target volume contours are included, which provide coverage of PAN nodes for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 16 publications
(12 reference statements)
2
29
0
Order By: Relevance
“…The authors found 12 of the 122 nodes were not fully covered by the CTV as defined by the RTOG guidelines (19). Recommendations for increased accuracy of paraaortic and inguinal nodal CTV contouring for conformal RT planning in patients with gynecological malignancies have been proposed by multiple studies (20,21,22).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The authors found 12 of the 122 nodes were not fully covered by the CTV as defined by the RTOG guidelines (19). Recommendations for increased accuracy of paraaortic and inguinal nodal CTV contouring for conformal RT planning in patients with gynecological malignancies have been proposed by multiple studies (20,21,22).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The anatomic diagrammatic sketch of the SCV nodes region is shown in Figure 1. The locations of the involved SCV nodes for all patients were then transferred onto a template CT image (registered by hand drawings from the diagnostic CT scan onto the template CT scan) according to methods previously described (19)(20)(21)(22). The volumetric center of each LN was identified and used for subsequent characterization of location.…”
mentioning
confidence: 99%
“…In the study of Keenan et al ( 67 ), all PALNs were inferior to the left renal vein. Takiar et al ( 68 ) reported that 96% of PALNs were in the inferior and middle third of the PALN region. In the retrospective study by Lee et al ( 33 ), 96 patients received prophylactic sub-renal vein radiotherapy.…”
Section: Delineation and Dose Prescription Of The Paln Regionmentioning
confidence: 99%
“…Most PALNs are located in the LLPA and AC regions. Only 4–6% of PALNs are located in the PRC region ( 67 , 68 , 70 ). As LNs in the PRC region are rare and the mean distance from the inferior vena cava to LNs in the PRC region is small, it is reasonable that the node CTV expansion from vessels can be small in the PRC region.…”
Section: Delineation and Dose Prescription Of The Paln Regionmentioning
confidence: 99%
See 1 more Smart Citation